County-level estimates of population and economic scenarios under the shared socioeconomic pathways: A case study in Inner Mongolia, China. (June 2021) - Bai, Yuping; Wang, Wenxuan; Hu, Yecui; Wang, Zehao
Abstract: Contribution from socio-economic development to climate change cannot be ignored. In order to make a more reasonable comprehensive assessment of the future climate change, the Intergovernmental Panel on Climate Change (IPCC) has proposed the Shared Socioeconomic Pathways (SSPs) based on the background of climate change and the possible future socio-economic conditions, which describes the adaptation and mitigation challenges of climate change. Based on different SSP scenarios, combined with China's current population policy and the actual social and economic development in Inner Mongolia, this paper adopts PDE model and C-D model to simulate population and economic changes of various counties in Inner Mongolia from 2010 to 2050. It is founded that population and GDP varies from different counties significantly, and shows the patterns of high in east and low in west, high in south and low in north. The spatial distribution of GDP is positively related with the population. The total population increases first and then decreases from 2015 to 2050 in Inner Mongolia. By the ends of 2050, the population reaches 23.32 million (−9.46%), 24.14 million (−2.30%), 24.72 million (+0.05%), 22.37 million (−9.46%), 23.49 million (−4.93%) under SSP1, SSP2, SSP3, SSP4, SSP5 scenarios. The largest gap of population is 2.35 million between SSP3 and SSP4. The GDP grows constantly from 2010 to 2050 in Inner Mongolia, but the growth rate is slowing down. By the ends of 2050, GDP reaches 5.09 trillion (+4.75 times), 5.22 trillion (+4.90 times), 4.41 trillion (+3.98 times), 4.98 trillion (+4.62 times), 5.87 trillion (+5.63 times). Therein, the biggest gap of GDP is 1.5 trillion between SSP4 and SSP5. The results provide technical solution for population and economic projection under SSPs at small area and subnational level, and provides scientific basis for the formulation of climate change policies in order to formulate measures to deal with climate change risks. Highlights: Population and GDP of 101 counties in Inner Mongolia are predicted under SSPs. Population and GDP are high to low from east to west and south to north. The largest gap of population is 2.35 million between SSP3 and SSP4 in 2050. The largest gap of GDP is 1.5 trillion between SSP4 and SSP5 in 2050. The spatial distribution of GDP is positively related with the population.